Pengendalian Penyimpangan Pemanfaatan Ruang di Kawasan Pesisir Pantai Kota Makassar - Firdaus; Nini Apriani Rumata; Rizka Damayanti; M. Ansyari Syamsuddin B (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2022)
The coastal area of ​​Makassar city provides productive natural resources both as a source of food, mineral and energy mining, communication media as well as recreation or tourism areas, this has consequences in managing various existing potentials, especially coastal areas, and overcoming the obstacles and challenges faced. The purpose of the study is to explain the factors that influence the occurrence of spatial utilization deviations and how to control space utilization deviations. The location of the research was carried out in the Coastal Area, Tamalanrea District, Makassar City, which experienced a very fast and rapid process of land use change, it was suspected that there was various land uses as magnets that could attract the growth and development of other land use activities. The method used consists of the observation method and the Questionnaire method in a qualitative-quantitative descriptive analysis through a cross-tabulation approach and a descriptive analysis of Law Number 26 of 2007 concerning Spatial Planning. The factors that influence the occurrence of spatial use deviations in the coastal area of ​​Tamalanrea District are the substance of the spatial plan, the rules/stipulations factor, the process, and procedure factor, the institutional factor, and the unavailability of the standard and technical rules for the use of space. As well as the absence of a detailed spatial plan for Makassar City, it is difficult to control the use of space in the Coastal Area of ​​Tamalanrea District.